Programas sociais: Efetividade, eficiência e eficácia como dimens\~oes operacionais da avaliaç\~ao - Alexandre Marinho; Luis Otávio Façanha (Instituto de Pesquisa Econômica Aplicada (IPEA), 2001)
– This paper tries do motivate the discussion of evaluation problems in the context of social programs. Initially, the text explores the point of view that social programs should be recognized as complex organizations. In the case, there are multiple objectives, decentralization, and coordination problems demanding high managerial efforts. The paper borrows orientations from the theory of contracts, and proposes data envelopment analysis (DEA) as a useful tool to assess relative efficiency of agents and of specific programs. DEA is also defended as a possible technique to assess budgeting rules, and as a support to virtuous incentive schemes to agents.
Keywords: 330; Sozialpolitik; Wirkungsanalyse; Vertragstheorie; Data-Envelopment-Analyse; Theorie